EDUCATION ON HEALTHY, SAFE, AND NUTRITIOUS LOCAL FOOD THROUGH THE NUTRITION GO TO SCHOOL (NGTS) SCHOOL GARDEN PILOT MODEL IN CIREBON CITY - Wiwit Estuti; Uun Kunaepah; Isnar Nurul Alfiyah (Jurnal Abdisci, 2024)
School is a very effective place for learning and character formation of students. Knowledge, attitudes and behaviors in choosing, processing and consuming food are greatly influenced by education in schools. Schools that have a school garden are an important component and greatly contribute to realizing healthy students. The school has sought the availability of a nutrient garden in the school during the NGTS Community Service activity carried out with SEAMEO in 2019. NGTS activities have contributed with the existence of model school gardens in 4 (four) locations, namely SMPN 7, SMPN 5, SD Sidamulya and SD Pahlawan in Cirebon City, in addition to the cooperation between various related service sectors in the implementation of NGTS. Partnership community service activities (PKM) are in the form of education and assistance in making safe, healthy, nutritious food made from local ingredients so that video tutorials on how to make nuggets and recipe books for processed nuggets based on local food ingredients are obtained which can be used as a guide in making healthy, safe and nutritious food and made from local food that can be used as an example for other schools in the Cirebon city area. This activity was carried out using a combination of socialization and mentoring methods by involving students. The initial stage of this activity was the making of books on various processed nuggets, and the second stage was socialization by video tutorial method and distribution of books on various processed nuggets. Measuring nugget processing knowledge before and after distributing books and playing videos of nugget making. The outputs achieved from the PkM program are the book Miscellaneous Nugget Recipes processed from local food from school gardens and a video of the process of making Miscellaneous Nuggets (IPR). The conclusion of this PKM activity is that there is an increase in knowledge about nugget processing so as to help teachers and students in providing healthy, safe and nutritious food from school.